The biomedical securitization of global health - Jens Holst; Remco van de Pas (BMC, 2023)
Abstract Background The COVID-19 outbreak has shifted the course in the global health debate further towards health security and biomedical issues. Even though global health had already played a growing role in the international policy agenda, the pandemic strongly reinforced the interest of the media, the general public and the community in cross-border infectious diseases. This led to a strengthening of the already dominant biomedical understanding of global health and the securitization of health in foreign policy. Methods This paper critically provides a narrative, iterative review of the health security literature available to date, with a special focus on the development of the currently prevailing concept of health security and the dual trend towards the securitization and biomedicalization of global health. Findings In a world increasingly determined by power asymmetries, unequal distribution of opportunities and resources, and inadequate governance structures, securitizing health has become a key feature of global governance. Health security is predominantly based on a concept that neglects the global burden of disease determined by non-communicable conditions rather than by infectious diseases. Moreover, it exhibits a trend towards biomedical solutions and neglects root causes of global health crises. Conclusions As important as health security is, the underlying concept driven by biomedical and technocratic reductionism falls short. It widely neglects the social, economic, political, commercial and environmental determination of health. Beyond improved health care and prevention, health-in-all policies are ultimately required for ensuring health security and reducing one of its main challenges, health inequalities within and between countries. Global health security must first and foremost seek to guarantee the universal right to health and therefore emphasise the social, economic, commercial and political determination of health.